PEMAKNAAN NAMA HANTU JAWA DALAM MAJALAH PANJEBAR SEMANGAT TAHUN 2017-2019 - Winona Alma Della; Widhyasmaramurti Widhyasmaramurti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The discussion of ghosts is one of the topics that can be discussed anywhere and anytime. Ghosts in society are known as entities that have certain names and characteristics. One of the interesting things to research is the meaning of the Javanese ghost name. The name of Javanese ghost in this study was obtained from the article Alaming Lelembut in Panjebar Semangat Magazine in 2017-2019. This research aims to describe the meaning of Javanese ghost names. The meaning of Javanese ghost names was obtained using qualitative methods and Dijk’s (1980) theories of discourse analysis in Renkema (2004) through 3 rules, namely the rules of elimination, generalization, and construction. The results showed that there are 6 known Javanese ghost names, namely, Banaspati, Sundel Bolong, Peri, Bajang Kerek, Gendruwo, and Wewe Gombel. From those 6 names, there are 23 different meanings from one ghost to another and 6 meanings are general. The difference in meaning in the names of Javanese ghosts is caused by the influence of ideas or ideas contained in the minds of Javanese people who are detailed and meticulous.